Perioperative Histologically Controlled Fistula Resection in Patients with Imperforate Anus and Perineal Fistula - Skaba, Richard; Dotlacil, Vojtech; Fuccillo, Pavla; Rouskova, Blanka; Pos, Lucie; Rygl, Michal (European journal of pediatric surgery, 2024)
INTRODUCTION: Postoperative constipation (PC) in patients with imperforate anus and perineal fistula (PF) has been reported in up to 60%. Histological studies of PF revealed innervation anomalies which seem to be one of the reasons for PC. Perioperative histologically controlled fistula resection (PHCFR) allows appropriate resection of PF and pull-down normoganglionic rectum at the time of posterior sagittal anorectoplasty (PSARP). MATERIALS AND METHODS: A total of 665 patients with anorectal malformations underwent surgery between 1991 and 2021. Of these, 364 presented PF; 92 out of them (41 F) were studied. Patients with sacral and spinal cord anomalies, neurological disorders, and cut-back anoplasty were excluded. PSARP was done on all patients. Hematoxylin-eosin staining and NADH Tetrazolium-reductase histochemical method were used. Four and more ganglion cells in the myenteric plexus represented a sufficient length of the resection. The continence was scored according to the modified Krickenbeck scoring system. Final scores ranged from 1 to 7 points. Values are given as median. RESULTS: A total of 65 (70.7%) patients presented an aganglionic segment in PF, and 27 patients presented hypoganglionosis. The median length of the resected fistula was 25 mm (interquartile range [IQR]: 20-30). The median total continence score was 7 (IQR: 6-7). Post-op constipation was observed in 6/92 (6.5%) patients. CONCLUSION: PHCFR diminished PC to 6.5% of patients.
Keywords: Perineum; novorozenec; Infant, Newborn; Rectal Fistula; Humans; Infant; rektální píštěl; kojenec; dítě; Child; zácpa; Female; Rectum; Constipation; výsledek terapie; perineum; lidé; Plastic Surgery Procedures; předškolní dítě; Postoperative Complications; pooperační komplikace; ženské pohlaví; zákroky plastické chirurgie; Anus, Imperforate; Male; anální atrézie; Retrospective Studies; Treatment Outcome; retrospektivní studie; rektum; mužské pohlaví; Child, Preschool